The common diabetes drug metformin can diminish the action of citral against Rhabdomyosarcoma cells in vitro. (14th October 2020) - Duan, Chengchen; Evison, Anna; Taylor, Lucy; Onur, Simone; Morten, Karl; Townley, Helen
Abstract : Rhabdomyosarcoma (RMS) is a rare type of soft tissue sarcoma most commonly found in pediatric patients. Despite progress, new and improved drug regimens are needed to increase survival rates. Citral, a natural product plant oil can induce cell death in cancer cells. Another compound, metformin, isolated originally from French lilac and used by diabetics, has been shown to reduce the incidence of cancer in these patients. Application of citral to RMS cells showed increase in cell death, and RD and RH30 cells showed half maximal inhibitory concentration (IC50 ) values as low as 36.28 μM and 62.37 μM, respectively. It was also shown that the citral initiated cell apoptosis through an increase in reactive oxygen species (ROS) and free calcium. In comparison, metformin only showed moderate cell death in RMS cell lines at a very high concentration (1, 000 μM). Combinatorial experiments, however, indicated that citral and metformin worked antagonistically when used together. In particular, the ability of metformin to quench the ROS induced by citral could lead to the suppression of activity. These results clearly indicate that while clinical use of citral is a promising anti‐tumor therapy, caution should be exercised in patients using metformin for diabetes.